Pengaruh Self-Regulated Learning terhadap Stres Akademik pada Mahasiswa Tingkat Akhir - Humairah Muthmainah Rif'atuzzahidah; Dewi Rosiana (Bandung Conference Series: Psychology Science, 2024)
Abstract. Self-regulated learning means that these skills do not develop spontaneously, meaning that self-regulated learning in individuals can change or not persist. These changes can be caused by increased academic demands. For final year students, a thesis is a task that must be completed and there are demands for completion, namely to do it independently and graduate on time. These academic demands can cause academic stress. Therefore, independent learning is needed in the learning process. The aim of this research is to determine the level of self-regulated learning and academic stress and to determine the effect of self-regulated learning on academic stress in final year students working on their thesis. The research method used is a quantitative method with data analysis using a simple linear regression test. The total sample was 203 respondents (68% female and 32% male) final year students who were working on their thesis. The sampling technique used is convenience sampling. Data were obtained using the self-regulated learning scale and the Student-Life Stress Inventory (SLSI). The research results showed that there was an influence between self-regulated learning and academic stress on final year students working on their thesis (T test 0.000<0.05 and R2 value 0.451). Independent learning is at a low level and academic stress is at a high level. This is a suggestion for future researchers to expand the amount of research in various faculties and universities to provide programs that can increase learning independence and reduce academic stress. Abstrak. Self-regulated learning merupakan keterampilan tidak berkembang secara spontan, artinya self-regulated learning pada individu dapat berubah-ubah atau tidak menetap. Perubahan tersebut dapat disebabkan oleh tuntutan akademik yang meningkat. Pada mahasiswa tingkat akhir skripsi merupakan tugas yang harus dijalani dalam penyelesaiannya terdapat tuntutan, yaitu dilakukan secara mandiri dan lulus tepat waktu. Adanya tuntutan akademik tersebut dapat menyebabkan stres akademik. Oleh karena itu, self-regulated learning dibutuhkan dalam proses pembelajaran. Tujuan penelitian ini adalah untuk mengetahui tingkat self-regulated learning dan stres akademik dan mengetahui pengaruh self-regulated learning terhadap stres akademik pada mahasiswa tingkat akhir yang mengerjakan skripsi. Metode penelitian yang digunakan adalah metode kuantitatif dengan analisis data menggunakan uji regresi linear sederhana. Jumlah sampel 203 responden (68% Perempuan dan 32% laki-laki) mahasiswa tingkat akhir yang sedang mengerjakan skripsi. Teknik sampling yang menggunakan adalah convenience sampling. Data diperoleh menggunakan skala self-regulated learning dan Student-Life Stress Inventory (SLSI). Hasil penelitian didapatkan terdapat pengaruh antara self-regulated learning dan stres akademik pada mahasiswa tingkat akhir yang mengerjakan skripsi (Uji T 0.000<0.05 dan nilai R2 0.451). Self-regulated learning berada di tingkat rendah dan stres akademik berada di tingkat tinggi. Adapun saran bagi peneliti selanjutnya untuk memperluas jumlah sampel penelitian di berbagai fakultas dan universitas dapat memberikan program yang dapat meningkatkan self-regulated learning dan menurunkan stres akademik.